The Great Silence: The Science and Philosophy of Fermi’s Paradox by Milan M. Ćirković - Broderick, Damien (Journal of Scientific Exploration, 2019)
SETI, the Search for Extraterrestrial Intelligence, used to seem the cutting edge of available mystery. The Milky Way galaxy is immense, perhaps 400 billion stars, and the entire visible universe holds perhaps hundreds of billions of similar galaxies. If life on Earth is a product of evolution, there must be billions of billions of worlds inhabited by creatures ranging from bacteria to intelligent, conscious alien people, all distinct in form but converging on civilizations capable of listening for radio evidence of others near or preposterously far in space and time, and peppering the heavens with their own messages. If they are there, some nearby will have been able to pick up a century and more of electronic signals tearing out from our world at the speed of light. Yet we hear no faintest answer, no trace of them Out There. Why? Where are they? asked Nobelist Enrico Fermi in 1950, lunching with colleagues, toying with the mid-century hysteria over flying saucers. If our understanding of science is correct, “they” must be there, in profusion if not in UFOs. With this confidence in mind, SETI was established 35 years ago, nearly half a human lifetime, to listen and look for them. After the intervening decades, though, with ever-improving equipment, we still do not detect them. It’s a paradox! It’s “Fermi’s Paradox.” A Serbian astrobiophysicist and astronomer, Milan M. Ćirković, PhD, is a Senior Research Associate at the Astronomical Observatory of Belgrade and Assistant Professor of the Department of Physics at the University of Novi Sad in Serbia and Montenegro. On the evidence of this remarkable book, he is an ingenious polymath who shows little patience with SETI researchers who (he claims) fail to keep up with new data, displaying a kind of privileged narrow vision, or perhaps self-protection, in clinging to defunct theories of galaxies and their improbably absent inhabitants. Again, then: Where are they?